Bridging the Managerial Competency Gap in Purchasing Management: A Survey of Managers to explore Current vs. Expected Competencies Analysis - Zuzanna SIKORSKA (Communications of International Proceedings, 2024)
The aim of the study is to present the results and description of the direct study relating to evaluating managerial competencies in purchasing. The motive behind the study was the growing need to focus on the competencies of purchasing managers due to the changing business environment and particular attention was paid to answering the question which competencies are key in the area of ​​purchasing and in the implementation of everyday responsibilities of Purchasing Department employees. The answers to the research questions were obtained on the basis of the results of surveys conducted using the CAWI method based on the original questionnaire and the statistical method (factor analysis). Purposive sampling was used in the study. In-depth research focused on identifying statistically significant relationships in the explored topic. The study covered the group of experts with a minimum of 5 years of professional experience in the field of purchasing.The insights gained from this research could inform the development of a profile for an effective purchasing manager within an organization. The study provided that managerial competencies are key to success of any organisation and confirm that the respondents have a set of features directly related to the topic of the study, as well as the required work experience in the current company.
Keywords: managerial competencies; competency gap; purchasing; key competencies